Trypanosomiasis challenge estimation in The Gambia using the Berenil index: Comparison between zebu and N'Dama - Claxton, R.R.; Leperre, P.; Rawlings, P.; Snow, W.F.; Dwinger, R.H. (OAU/STRC, 1991)
The Berenil provides a means of estimating the trypanosomiasis challenge presented to cattle independent of, and therefore complementary to, the collection of tsetse data and of prevalence rates of infection in cattle. In areas where trypanotolerant cattle predominate, the Berenil Index has seldom been used as an independent assessment of trypanosomiasis challenge. An experimental protocol applied to sentinel herds of trypanotolerant and trypanosusceptible cattle in three regions of different tsetse challenge in The Gambia is described. Problems associated with the standardisation of the procedure are discussed and interim results are presented. The different challenges as measured by the Berenil Index are compared with those of tsetse derived data, and also compared to the trypanosome prevalence in local cattle. The Berenil Indices produced correspond well with these methods of estimating challenge. Indices range from no treatments per year to in excess of monthly treatments, depending on region and on breef of animal. The trypanosusceptible breed shows higher indices than trypanotolerant animals. Possible explanations for this difference are discussed.